Aggregation effects on flow and heat transfer of nanofluids over curved stretching/shrinking surface with Lorentz forces. (June 2023) - Ullah, Basharat; Wahab, Hafiz Abdul; Khan, Umar; Bhatti, Saira
Magnetohydrodynamic, mass suction improves the efficiency of aggregation effects on flow and heat transfer of nanofluids over curved stretching/shrinking surface with Lorentz forces are explored in this research study, which is two-dimensional. In order to solve the partial differential equations, the similarity transformation is used to translate them into ordinary differential equations. Numerical analysis of the model is performed using RK- 4 technique coupled with the shooting technique. The local Nusselt number, velocity, and temperature profiles, as well as the skin friction coefficient, are all now being studied. The solution can be found by analyzing a precise range of characteristics, such as stretching/shrinking, suction, and curvature. These metrics critical values fall as the nanoparticle volume fractions increase, indicating that they are becoming more stable.